Physicochemical And Organoleptic Quality Testing Of Millet Microgreen Juice (Panicum Miliaceum L.) On Different Milet Types And Plant Age - Kurnia Praise Sustainable, Indah; Kurnia Hartati, Fadjar; Andika Prayudanti, Adhania; Hariyani, Nunuk (Demeter: Journal of Farming and Agriculture, 2024)
This research has taken place using experimental laboratory methods of quantitative analysis. The variables used include varieties consisting of yellow millet and red millet, and plant life ranging from 6 days, 9 days, 12 days, and 15 days. The data obtained was analyzed based on parametric statistics using ANSIRA, using statistical product and service solution (SPSS) with version 24 and determining best treatment using effectiveness tests and determining antioxidant levels of best treatment. Different types and ages of plants have very real effects on reduced sugars, phenols, vitamin C, flavonoids and total soluble solids. Significant treatment between different plant types and ages resulted in a 6-day-old ryellow millet (MG1) being the best treatment with a result value (NH) of 0.73 with the parameter criterion reduction sugar level of 1.48%, total phenol content of 27.26 mg GAE/100mg, vitamin C 2.05 mg/100 mg, total flavonoid content of 4.98 mg QE/100 Mg, TPT 11.36 mg/L, color 4.81 (neutral), flavor 5.16 (few likes) and aroma 5.4 (few likes).